Legal Protection for Debtors in the Execution of Fiduciary Objects in Indonesia - Lodewijk, Dewi Putriani Yogosara; Santoso, Aris Prio Agus; Muftiyanto, R. Taufik Nur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In financing agreements, the phenomenon of debtors defaulting is very possible or occurs, so this causes creditors to take steps such as parate execution by using coercive debt collector services. This is justified because it is under the legal umbrella of the Fiduciary Guarantee Law. After the judicial review of Constitutional Court Decision No. 18/PUU-XVII/2019, the execution parate was abolished and the execution of fiduciary guarantee objects must be carried out by submitting a request for execution to the head of the district court, but in the case of Decision Number 157/Pdt.G/2021/Pn Skt, the judge actually rejected the plaintiff's petitum as a debtor who argued that the execution parate by the defendant (creditor) was an unlawful act. The formulation of the problem in this research is how to analyze the judge's legal considerations in determining whether the execution of fiduciary guarantees is valid in Decision Number 157/Pdt.G/2021/Pn Skt? And how is legal protection for debtors related to Constitutional Court Decision Number 18/PUU-XVII/2019? This research is included in the type of normative juridical research with a statutory approach. The purpose of this research is to determine the analysis of the judge's legal considerations in determining the validity of the execution of fiduciary guarantees in Decision Number 157/Pdt.G/2021/Pn Skt and to determine the legal protection for debtors in connection with Constitutional Court Decision Number 18/PUU-XVII/2019. The theoretical benefit of this research is a contribution to legal science, while the theoretical benefit is aimed at legal practitioners. The results of this research are that the plaintiff is not a party who voluntarily surrenders the object of the fiduciary guarantee and is not a party bound by an agreement to determine default, so the judge was wrong in rejecting the plaintiff's petitum which argued that the defendant was valid in the execution parate, and legal protection for the debtor was linked to Constitutional Court Decision Number 18/PUU-XVII/2019 is contained in Article 23 paragraph (2) and the plaintiff can take legal action to appeal solely to seek correction of the results of a decision that is considered wrong.